Los programas radiales con contenido edu-comunicativo y su incidencia en la adopción y preservación de las prácticas axiológicas de las familias lojanas - Diaz Pineda, Sandra Patricia (2016)
This research thesis is based on media education which is called common of interdisciplinary studies that address the theoretical and practical two historically separate disciplines dimensions: education and communication, why target was raised to know the influence of radio programming axiological practices lojanas families. Parents and young people have not listened to radio programs that help preserve family values and according to the results of surveys and focus groups both public wish that there is a radio programming with edu-communicative content collaborate to human values remain firm in our city. Through matrices contents and times of each program are identified; Surveys also applied to parents and young people; this focus group, where several families were gathered to add more information and interviews were conducted to professional psychology and social communication was added. The results of the applied techniques revealed that many people were unaware that broadcasters transmit an educational program on family values, and they would like such programs are broadcast. Before this, he proposed a edu-communicative program, which offers a different content to people and is motivation for the families of the city.